Characteristics of the smallest brucellaphage with strong lytic ability - Liu, Hongbaiyu; Zhong, Youhong; Zhang, Zhihong; Xu, Kehong; Mao, Chunpeng; Yang, Qiuju; Yang, Lihua; Yu, Binbin; Long, Ying; Qin, Xinyu; Shi, Liyuan; Chang, Sheng; et al. (Frontiers in Veterinary Science, 2025)
Brucellosis is a globally prevalent zoonotic disease caused by Brucella spp. posing significant threats to animal and human health. In this study, a novel lytic brucellaphage designated Y17 was isolated from sheep fecal samples collected in Ludian County, Yunnan Province, China. Transmission electron microscopy revealed that Y17 was composed of an icosahedral head (48.1 ± 2 nm) and a short tail (10.8 ± 1 nm), making it the smallest brucellaphage described so far. The optimal multiplicity of infection (MOI) for phage Y17 is 0.001, with a burst size of ~187 PFU/cell, the largest value reported for any brucellaphage, and it has a relatively short latent period. It exhibits broad pH and temperature stability, retaining activity even after 1 h of exposure to ultraviolet radiation and various ethanol concentrations. Y17 shows strong lytic activity against Brucella abortus and can also infect some Brucella melitensis strains. The Y17 genome spans 38,025 bp with a GC content of 48.2%, making it the smallest genome among brucellaphages to date. It lacks virulence, antibiotic resistance, or lysogenic genes, indicating its potential as a safe biocontrol agent. Whole-genome average nucleotide identity (ANI) analysis reveals high homology across all lytic brucellaphages, but Y17 exhibits relatively lower genome coverage compared to other lytic brucellaphages. Genomic collinearity comparison revealed that Y17 lacks some terminal fragments present in the genomes of other lytic brucellaphages. Furthermore, compared to brucellaphages with genomes larger than 40 kb, Y17 also lacks segments corresponding to ORF21 (amidase), ORF28 (hypothetical protein), and ORF29 (carbohydrate-binding protein). Phylogenetic analysis indicates that Y17 is closely related to phages Iz, Bk2, S708, Wb, R/C, Pr, and Bk. Moreover, the capsid gene shows significantly higher conservation in comparison with the tail collar and amidase genes. This study significantly enriches the brucellaphage database and highlights the potential of Y17 as a biocontrol agent for managing brucellosis in endemic regions.